2011
DOI: 10.1089/neu.2010.1660
|View full text |Cite
|
Sign up to set email alerts
|

Role of Spared Pathways in Locomotor Recovery after Body-Weight-Supported Treadmill Training in Contused Rats

Abstract: Body-weight-supported treadmill training (BWSTT)-related locomotor recovery has been shown in spinalized animals. Only a few animal studies have demonstrated locomotor recovery after BWSTT in an incomplete spinal cord injury (SCI) model, such as contusion injury. The contribution of spared descending pathways after BWSTT to behavioral recovery is unclear. Our goal was to evaluate locomotor recovery in contused rats after BWSTT, and to study the role of spared pathways in spinal plasticity after BWSTT. Forty-ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 57 publications
2
41
0
2
Order By: Relevance
“…116 For this reason, there are new approaches that aim to improve locomotor function by increasing effectiveness of the spared corticospinal or corticoreticulospinal pathways. 117 This premise has been tested in an operant conditioning training program in humans targeting improved volitional control of ankle dorsiflexion.…”
Section: Targeting Supraspinal Structuresmentioning
confidence: 99%
“…116 For this reason, there are new approaches that aim to improve locomotor function by increasing effectiveness of the spared corticospinal or corticoreticulospinal pathways. 117 This premise has been tested in an operant conditioning training program in humans targeting improved volitional control of ankle dorsiflexion.…”
Section: Targeting Supraspinal Structuresmentioning
confidence: 99%
“…Various studies in experimental animals uncovered a mosaic of injury-induced molecular and cellular changes in segments caudal to a SCI (Krenz and Weaver, 1998;Ballermann and Fouad, 2006;Kitzman, 2006Kitzman, , 2007Soares et al, 2007;Hou et al, 2008;Tan et al, 2008;Hou et al, 2009;Boulenguez et al, 2010;Murray et al, 2010;Ichiyama et al, 2011;Singh et al, 2011;Kapitza et al, 2012;Tan et al, 2012). Depending upon the SCI model and specific functional assessments, these alterations in the properties of neuronal circuits have alternatively been classified as beneficial or detrimental.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported a beneficial effect of treadmill training in spinally contused rats [47,68]. However, such benefits do not result when high levels of robotic assistance are applied during the training [46].…”
Section: Limitationsmentioning
confidence: 99%